Managing climate change crisis events at the destination level. (December 2021) - Prideaux, Bruce; Thompson, Michelle; Pabel, Anja; Cassidy, Leonie
Abstract: The objectives of this research were to firstly, identify visitors' concerns about the impacts of climate change on the Great Barrier Reef (GBR) Australia, and secondly, use these findings to identify new mechanisms that assist destinations to respond to future crisis events. A survey of 851 domestic and international visitors to Cairns, Australia, indicated significant concerns about the future of the GBR, which may lead to a future crisis due to falling demand. As crisis events usually affect the destination as a whole, we adopted a learning destination perspective on the basis that community support for workable solutions is more likely to occur when all members of the destination community work collaboratively. Key contributions of this research are identifying visitors' concerns about the impacts of climate change on the GBR, and extending the learning destination approach by incorporating it into Faulkner's crisis management model, with a specific focus on proactively responding to a known future crisis event. The paper offers a novel approach to respond to climate change using critical studies and theoretical contributions that extend existing literature on crisis management at the destination level.